Interpreter-Mediated Neuropsychological Testing of Monolingual Spanish Speakers - Casas, Rachel (2011)
The primary objective of this study was to investigate empirically whether using an interpreter to conduct neuropsychological testing of monolingual Spanish speakers affects test scores. Participants included 40 neurologically normal Spanish-speakers with limited English proficiency, ages 18–65 years (M= 39.7, SD =13.9), who completed the Vocabulary, Similarities, Block Design, and Matrix Reasoning subtests of the Wechsler Adult Intelligence Scale-III in two counterbalanced conditions: with and without an interpreter. Results indicated that interpreter use significantly increased scores on Vocabulary and Similarities. However, scores on Block Design and Matrix Reasoning did not differ depending upon whether or not an interpreter was used. In addition, the findings suggested a trend toward higher variability in scores when an interpreter was used to administer Vocabulary and Similarities; this trend did not show up for Block Design or Matrix Reasoning. Together, the results indicate that interpreter use may significantly affect scores for some tests commonly used in neuropsychological practice, with this influence being greater for verbally mediated tests. Additional research is needed to identify the types of tests that may be most affected as well as the factors that contribute to the effects. In the meantime, neuropsychologists are encouraged to avoid interpreter use whenever practically possible, particularly for tests with high demands on interpreter abilities and skills, with tests that have not been appropriately adapted and translated into the patient’s target language, and with interpreters who are not trained professionals.